Inteligência arquivística: um conceito à luz da teoria fundamentada em dados - CAVALCANTE, Celineide Rodrigues (Universidade Federal do Pará, 2023)
Archival Intelligence, translated in this research as Archival Intelligence, presents a growing scientific production internationally, still little explored in Brazil. Archival Intelligence is related to the knowledge and skill set of archival users for effective research with primary sources. Thus, the objective of this work is to propose a concept for Archival Intelligence suitable for the national scenario, with the delimitation of characteristics, contexts and subjects involved, in order to broaden and consolidate the discussions around Information Literacy with Archival Science in Brazil. We elected as methodological options: Systematic Bibliographic Review to identify the presence of the term Archival Intelligence in publications indexed in the Journal Portal Coordination for the Improvement of Higher Education and Grounded Theory to propose the concept of Archival Intelligence. The results of this research point to the importance of transversality among Information Literacy, Information Literacy in Archival Science, Archival Literacy and Archival Intelligence to deepen the studies on archival instruction, foster the creation of teaching and learning standards with primary sources and infer their practical application to archival users. It is necessary the archivist's protagonism in this process, as well as his partnership with information professionals, researchers, teachers and students from different areas.